Experimental investigation of CoFe_2O_4 particle size and acoustic properties of magnetic fluid - Zieliński, Bartek; Skumiel, A.; Józefczak, A. (Archives of Acoustics, 2006)
In this paper magnetic particle size and acoustic properties of the ferrofluid with CoFe_2O_4 particles are presented. The results acquired from atomic force microscope measurements will let us set average value for the hydrodynamic diameter of magnetic particles appearing in CoFe_2O_4 ferrofluids. The knowledge of these sizes is extremely useful because on the further stage of examinations it allows us to determine the size of surfactant coating particles. It is possible by making additional magnetic measurements enabling the size of average magnetic core contained in the ferrofluid. Also, it allows us to determine in a simple way the thickness of the surfactant layer. Such information on magnetic particles in a given ferrofluid is very valuable in the context of the application of the liquids either in technology or in medicine. Moreover, ultrasonic measurements carried out are providing the valuable information for us on the subject of the ferrofluid stability exposed to the action of the external magnetic field. The experimental estimation of the ultrasonic wave absorption coefficient in the function of a field for a few temperatures allows us to forecast how magnetic particles in a given magnetic liquid are capable of joining together and creating clusters, and how big aggregates can be created in this way.